In-situ Monitoring System Equipped with FT-IR and QMS and Thermal Decomposition of Zr(NCH3C2H5)4 Precursor. (16th August 2016) - Park, In-Sung; Seong, Sejong; Jung, Yongchan; Lee, Taehoon; Ahn, Jin-Ho; An, Jong-Ki; Yun, Juyoung
Abstract : An in-situ monitoring system equipped with both fourier transform infrared (FT-IR) spectroscopy and quadrupole mass spectroscopy (QMS) was introduced and measured the decomposition of Zr(NCH3 C2 H5 )4 precursor, which usually used in ALD of ZrO2 films. For the actual influence of the decomposition state of the metalorganic precursor on the properties of the produced film, Zr(NCH3 C2 H5 )4 precursor was heated in the temperature ranges from 100 °C to 200 °C by the step of 25 °C. As a decomposed reference, the acquisition FT-IR and QMS data at 500 °C was used and compared with those at lower temperature. The increase of IR peak at 2962 cm -1 due to C-H in CH3 ligands and the generation of peak at 711 cm -1 due to N-H bonds were useful to monitor the decomposition of Zr(NCH3 C2 H5 )4, where the latter stated to appear from 125 °C, indicating the onset temperature of decomposition.